1997
DOI: 10.1084/jem.186.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Chemokine Receptors to the Leading Edge during Lymphocyte Chemotaxis

Abstract: Leukocyte migration in response to cell attractant gradients or chemotaxis is a key phenomenon both in cell movement and in the inflammatory response. Chemokines are quite likely to be the key molecules directing migration of leukocytes that involve cell polarization with generation of specialized cell compartments. The precise mechanism of leukocyte chemoattraction is not known, however. In this study, we demonstrate that the CC chemokine receptors CCR2 and CCR5, but not cytokine receptors such as interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
153
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 28 publications
8
153
2
Order By: Relevance
“…Because CCR2 is expressed by many cell types that may infiltrate inflamed skin, including macrophages and T cells 29 , the LC deficiency that was detected early after UV-irradiation may reflect a requirement for CCR2 in other hematopoietic cell types involved in LC development. To test whether the requirement for CCR2 was intrinsic to the LC precursor, we followed the reconstitution of mutant and wild-type LCs generated from mixed BM cells (1:1 CCR2 −/− :CCR2 +/+ ) in the same UV-irradiated animals.…”
Section: Role Of Ccr2 In the Recruitment Of Lc Precursorsmentioning
confidence: 99%
“…Because CCR2 is expressed by many cell types that may infiltrate inflamed skin, including macrophages and T cells 29 , the LC deficiency that was detected early after UV-irradiation may reflect a requirement for CCR2 in other hematopoietic cell types involved in LC development. To test whether the requirement for CCR2 was intrinsic to the LC precursor, we followed the reconstitution of mutant and wild-type LCs generated from mixed BM cells (1:1 CCR2 −/− :CCR2 +/+ ) in the same UV-irradiated animals.…”
Section: Role Of Ccr2 In the Recruitment Of Lc Precursorsmentioning
confidence: 99%
“…The polarized T cell is already spatially organized in terms of its response to antigen, as the leading edge is more sensitive to CD3 stimulation than the trailing edge, denoting that TCRs are localized to the front edge of the cell [7]. Treatment of T lymphocytes with chemokines or other chemotactic agents leads to the recruitment of CCRs such as CCR2 and CCR5 to this leading edge [8]. Apparently, receptors involved in sensing chemotactic gradients are preferentially localized to the leading edge in a polarized cell.…”
Section: A Role For Chemokines In the Recruitment And Polarization Ofmentioning
confidence: 99%
“…Previous reports have suggested that chemokine receptors on lymphocytes redistribute to the leading edge of polarized migrating cells in response to a soluble, chemotactic ligand (12) and that ligation of chemokine receptors induces the lateral movement of ␤ 2 integrins on lymphocytes (11). Therefore, we hypothesized that chemokine receptors may colocalize with integrins.…”
Section: Reorganization Of Ccr6 and Colocalization With ␤ 2 Integrin mentioning
confidence: 99%
“…Notably, inhibitors of integrin lateral mobility (i.e., calpeptin) block adhesion of lymphocytes to ICAM-1 at low, but not high, site densities (11). Also, chemokine receptors on T cells polarize in response to ligand and cluster at the leading (migrating) edge of the cell (12), although neutrophils do not show this response and may redistribute intracellular molecules such as the AKT protein kinase to the migrating edge of the cell (13).…”
mentioning
confidence: 99%